2010
DOI: 10.1007/s13244-010-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive image-guided therapy for inoperable hepatocellular carcinoma: What is the evidence today?

Abstract: Hepatocellular carcinoma (HCC) is a primary malignant tumor of the liver that accounts for an important health problem worldwide. Only 10–15% of HCC patients are suitable candidates for hepatic resection and liver transplantation due to the advanced stage of the disease at time of diagnosis and shortage of donors. Therefore, several minimally invasive image-guided therapies for locoregional treatment have been developed. Tumor ablative techniques are either based on thermal tumor destruction, as in radiofreque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…Recently, several percutaneous ablation techniques, such as radiofrequency ablation (RFA), microwave ablation, cryoablation and laser-induced interstitial thermotherapy, are employed in treatment of hepatocellular carcinoma (HCC) in cirrhosis. [1][2][3] Percutaneous RFA has gained great popularity in the treatment of HCC in cirrhosis. [4][5][6] Several studies have shown its efficacy and high reproducibility elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several percutaneous ablation techniques, such as radiofrequency ablation (RFA), microwave ablation, cryoablation and laser-induced interstitial thermotherapy, are employed in treatment of hepatocellular carcinoma (HCC) in cirrhosis. [1][2][3] Percutaneous RFA has gained great popularity in the treatment of HCC in cirrhosis. [4][5][6] Several studies have shown its efficacy and high reproducibility elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, radiologists typically compare the tumor region from preinterventional images to the ablation zone in post-interventional CT images to assess treatment success. [4][5][6] They mentally compare shape, size, and position of the tumor and the treated zone. For this evaluation, the treatment is considered successful if the tumor is completely enclosed by the ablation zone with a safety margin of 5 mm or larger.…”
Section: Introductionmentioning
confidence: 99%
“…The available data is sufficient to conclude that RFA significantly improves survival and decreases local recurrence when compared to PEI. PEI use should be limited to circumstances when RFA is unavailable or technically not possible [99,100] .…”
Section: Early Stage (Bclc A)mentioning
confidence: 99%